Meningkatkan Kemampuan Pemahaman Siswa Pada Penjumlahan dan Pengurangan Bilangan Melalui Model Pembelajaran Problem Based Learning (PBL) Pada Siswa Kelas II SD - Evi Purnama Bayu Ningsih; Patri Janson Silaban; Lasma Silaban (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aims of this research are: 1) to determine the application of the problem based learning model in addition and subtraction counting material in class 2 at SDN Kaloy, 2) to determine the increase in the ability to understand addition and subtraction in class 2 students at SDN Kaloy. This research method uses Arikunto's Classroom based action research PTK model. The subjects of this research were 20 grade 2 students at SDN Kaloy, Tamiang Hulu District. There were 2 cycles of action in this research (Cycle I and Cycle II). The data collection techniques used are planning, implementation, observation, reflection and documentation. The results of the research show that: 1) The application of the problem based learning model to the ability to calculate addition and subtraction was carried out in 2 cycles with different results. In Cycle I, the results of observing teacher activities were 87.5 (very good) and the results of observing student activities were 82.8 (good). Meanwhile, in Cycle II there was an increase, the results of observing teacher activities were 92 (very good) and the results of observing student activities were 89 (very good). 2) Improvement in the ability to calculate addition and subtraction of class 2 students at SDN Kaloy in Cycle I, the class average was 79 (fair) which had not yet reached the minimum performance indicator of 80. In Cycle II there was an increase in the class average, namely 86 (very good). The percentage of student learning completeness increased from Cycle I 64% to 84% in Cycle II with an increase of 20%.